2019
DOI: 10.1038/s41586-019-1311-3
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct modes of mitochondrial metabolism uncouple T cell differentiation and function

Abstract: Activated CD4 T cells proliferate rapidly and remodel epigenetically before exiting the cell cycle and engaging their acquired effector function. Metabolic reprograming from the naïve-state is required throughout these phases of activation1. In CD4 T cells, T cell receptor (TCR) ligation, along with co-stimulatory and cytokine signals induce a glycolytic anabolic program required for biomass generation, rapid proliferation, and effector function2. CD4 T cell differentiation (proliferation and epigenetic remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 34 publications
5
134
0
3
Order By: Relevance
“…Together, these data provide evidence that the regulation of pro-versus anti-inflammatory cytokine expression is regulated in a FAO-dependent manner in T regs . This adds to previous reports showing specific electron transport chain complexes differentially regulate proliferation and cytokine expression in Th1 T eff cells and provides evidence these two processes can be uncoupled metabolically ( 94 ).…”
Section: Resultssupporting
confidence: 76%
“…Together, these data provide evidence that the regulation of pro-versus anti-inflammatory cytokine expression is regulated in a FAO-dependent manner in T regs . This adds to previous reports showing specific electron transport chain complexes differentially regulate proliferation and cytokine expression in Th1 T eff cells and provides evidence these two processes can be uncoupled metabolically ( 94 ).…”
Section: Resultssupporting
confidence: 76%
“…Energy insufficiency in IECs enhanced susceptible to T-cell mediated cytotoxicity was observed in vivo with both chemical inhibition and IEC specific genetic ablation of SDHA studies. Thus succinate accumulation in IECs caused by SDHA reduction, i.e defect in mitochondrial complex II, is distinct from the mitochondrial defects observed in other contexts such as ischemia reperfusion model, LPS activated macrophages or in other mitochondrial complex deficiencies 21 22 32 . However, decreased NADH production by insufficient TCA cycle, a substrate for complex I reaction the starting point of ETC, could also secondarily contribute to further slowing down of the mitochondrial respiration and metabolic shutdown in the IECs caused by pathogenic T cells.…”
Section: Discussionmentioning
confidence: 73%
“…The results here show that human naïve CD8 + T-cells require both mitochondria and glycolytic energy production for successful activation and resulting clonal expansion. Previous studies demonstrated that T-cell expansion can be improved by certain metabolites being present upon antigen stimulation, and that memory T-cells have a more catabolic metabolic profile compared to that of effector cells which exhibit more anabolic metabolic profiles 5,11 . When we ablated mitochondrial activity in vitro , naïve CD8 + T-cells were unable to become activated or expand, resulting in T-cell death.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown T reg cells require mitochondrial complex III to maintain their regulatory gene expression and suppressive function 4 . Furthermore, the tricarboxylic acid cycle (TCA) is required for terminal effector function of T H 1 cells through succinate dehydrogenase (complex II), but the latter activity suppresses proliferation of activated mouse T H 1 CD4 + T-cells 5 .…”
mentioning
confidence: 99%